Non-invasive physical plasma improves conventional wound management of cut and bite wounds in wild European hedgehogs - Jürgen Eichler; Björn Rulik; Alexander Abazid; Matthias B. Stope (Scientific Reports)
Abstract Non-invasive physical plasma (NIPP) has been used effectively for wound healing in human medicine for over two decades. The advantages are that NIPP has few side effects, is painless and gentle on the tissue. The therapeutic effect is mediated by reactive oxygen species (ROS). Based on the biomedical effects known to date, it can be assumed that NIPP can also be used for wound treatment in non-human mammals. In this prospective, non-randomized monocentric clinical trial, 43 European hedgehogs with cut and bite wounds were treated with conventional wound management (CWM: 21 patients) and compared with 22 patients with CWM plus NIPP treatment (CWM + NIPP). Under NIPP treatment, patients showed no signs of pain, stress or discomfort, even after several applications. In 76% of CWM + NIPP patients, three or four NIPP applications were sufficient. In patients in the CWM + NIPP group, wound treatment was completed statistically significantly 6 d earlier (CWM: 19.0 d versus CWM + NIPP: 13.2 d; p = 0.0008). This wildlife clinical trial demonstrates that NIPP can be used to improve wound healing in wild European hedgehogs. It is conceivable that NIPP therapy could also lead to positive effects in other injured wild animals, domestic animals or livestock.